A study on the hepatoprotective effect of turmeric (Curcuma longa) extract on the liver histopathology of albino rats induced by sodium diclofenac - Hibur, Grasia Intan Praskawati; Amat, Anita Lidesna Shinta; Riwu, Magdarita; Telussa, Arley Sadra (Acta Biochimica Indonesiana, 2025)
Background: Diclofenac sodium, a widely used nonsteroidal anti-inflammatory drug (NSAID), causes significant hepatotoxicity through oxidative stress mechanisms. Turmeric (Curcuma longa L.), rich in curcuminoid antioxidants, may offer hepatoprotection. Objective: To evaluate the hepatoprotective effects of turmeric extract against diclofenac sodium-induced liver injury in rats. Methods: Twenty-eight male Sprague Dawley rats were randomly divided into four groups (n=7): normal control, negative control (diclofenac sodium 10 mg/kg BW for 7 days), and two treatment groups receiving diclofenac sodium followed by turmeric extract at 100 or 200 mg/kg BW for 14 days. Liver histopathology was assessed using hematoxylin-eosin staining. Data were analyzed descriptively. Results: Turmeric extract attenuated hepatocellular damage in a dose-dependent manner. The 200 mg/kg BW dose completely prevented necrosis, demonstrating superior hepatoprotection compared to 100 mg/kg BW. Conclusion: Turmeric extract exerts hepatoprotective effects against diclofenac-induced liver injury through attenuation of histopathological damage.